Community Involvement in Tourism Entrepreneurship: A Case Study in Tioman Island, Malaysia - Sharif, Norhafiza Md; Lonik, Ku‘Azam Tuan (International Journal of Multicultural and Multireligious Understanding, 2017)
The tourism sector is one of the major economic contributors to most countries. Island tourism is one of the important tourism products of a country and is able to catalyse socio-economic development for the local communities. In Malaysia, studies on local entrepreneurship development in Tioman Island has not been given much attention by researchers. To fill this gap, this study aims to provide information on the field of entrepreneurial tourism in Tioman Island. The main objective of this study is to identify the characteristics of the island community as a tourism entrepreneur and to analyse the problems and challenges faced by the island's tourism entrepreneurs. The findings show that the majority of entrepreneurs are male, aged between 25 to 44, receive education until secondary school and married. Most of the local tourism entrepreneurs run the food and beverage business and manage their businesses for 11 to 15 years and earn a monthly income of RM2001 to RM4000. The local tourism operators also face a few problems such as capital and finance, marketing, business management and infrastructure. At the same time, the entrepreneurs also expect collaboration from the government to play an important role in advancing the island's tourism industry. At the same time, local tourism entrepreneurs also expect cooperation from the government and other authorities to play a role in developing the island's tourism industry.